Urban-rural differentials in nutritional status of ageing in Bangladesh - Uddin, M. Taj; Akter, Momduha; Hossain, Mohammad Kamal; Raju, Mohammad Ali; Noor, M. Shah (International Journal Of Community Medicine And Public Health, 2021)
Background: The growth rate of elderly is the fastest in most of the developing countries including Bangladesh. Nutrition plays fundamental role in maintaining good health especially in old age. This study was an attempt to assess the nutritional status of elderly and to compare it with their location. Methods: A total of 400 elderly in urban and rural area of Sunamgonj district have been interviewed through a structured questionnaire during July to September, 2019. A person aged 60 and above is included in the sample. Body mass index (BMI), mini nutritional assessment (MNA) short form, descriptive statistics, and Chi square test for association have been used for data analysis. Results: The analysis revealed that 17 percent elderly were under-weight, 66 percent were normal nutrition, 13 percent were over-weight and 4 percent were obese. The prevalence of malnutrition was found to be 40 percent. The rural elderly were at more risk of being malnourished compared to urban elderly. The mean BMI and MNA score of urban elderly were significantly different from the rural elderly. Conclusions: The findings show that more proportion of urban elderly are over-weight and obese compared to rural elderly. Therefore, measures should be taken to improve the nutrition status of elderly especially in rural area.